PENGARUH DISIPLIN BELAJAR DAN KINERJA TUGAS RUMAH TERHADAP HASIL BELAJAR FISIKA SISWA KELAS VIII SMP MUHAMMADIYAH 1 PEKALONGAN TAHUN PELAJARAN 2012/2013 - Utama, Galih Ricky; Salim, M. Barkah (Jurnal Pendidikan Fisika, 2014)
Discipline is one thing that is important in achieving the maximum target in the learning process . Besides the performance of the task is an effort to instill a deeper concept in a subject matter . With the homework expected of students actively learn and be stimulated to enhance better learning , fostering initiative and are solely responsible bold . Sengganggnya so students use the time for things that support their learning by completing activities that are useful and constructive With discipline and performance of the duties expected student achievement in the field of study of physics can be optimal.                          The purpose of this study was to determine the effect of the discipline of learning and the performance of the duties of the learning outcomes of physics . This type of research is experimental . Collecting data using questionnaires and tests . The research was conducted at SMP Muhammadiyah 1 Pekalongan , randomly selected sample . The data analysis technique used is the calculation of the linear regression analysis . The results showed that the discipline of learning and administration tasks affect student learning outcomes , it is obtained from the results of hypothesis testing on the discipline of learning on learning outcomes in Fhit = 20.32 greater than t table at significance level α = 5 % Fdaf = 4 , 10 . While testing the hypothesis on the performance of the duties of the student learning outcomes obtained with Fdaf value = 48.67 greater than the significance level α = 5 % tdaf = 4.10 . After the authors conducted a study proved that the suspect had a significant influence between disciplines home learning and task performance on learning outcomes , the authors suggest to students to be more disciplined in learning activities , so that the learning outcomes that will be obtained will be better and in accordance with the expected . For teachers to further streamline the tasks given to the students , not just the task of completing a matter of course , but the task of creating a summary and demonstrate concepts learned in class.